SOSIALISASI UNTUK PENCEGAHAN STUNTING SEJAK DINI DI SMA NEGERI 1 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Yayuk Lestari; Annisa Anindya; Vitania Yulia; Diego Diego; Meqorry Yusfi (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
This activity aimed to educate students of SMA Negeri 1 Koto XI Tarusan, Pesisir Selatan, on stunting prevention, particularly regarding balanced nutrition, the dangers of cigarette smoke, and anemia in adolescent girls. The methods employed included interactive presentations, Focus Group Discussions (FGD), and interactive quizzes to motivate and assess participants' understanding. The activity was conducted on October 16, 2024, involving 30 12th-grade students. The main stages of the activity consisted of three sessions: delivering material, group discussions facilitated by mentors, and quizzes to evaluate comprehension. Additionally, iron supplement tablets were distributed to adolescent girls as a preventive measure against anemia. Monitoring was conducted to observe changes in students' understanding and behavior before and after the activity. The results indicated a significant increase in students' understanding of stunting, including its risk factors and long-term impacts on children's futures. Before the socialization, students had limited knowledge, particularly about the relationship between diet, smoking habits, and anemia with stunting risks. After the activity, they gained a better understanding of the importance of balanced nutrition and early prevention efforts. Other findings revealed irregular breakfast habits and high smoking rates among male adolescents. In conclusion, this activity successfully raised students' awareness of stunting prevention. The participatory approach, through discussions and interactive quizzes, effectively created a learning atmosphere that was both enjoyable and informative. The expected impact is to serve as an initial step toward behavioral changes that support the sustainable health of the younger generation.